2021
DOI: 10.1186/s12888-021-03439-0
|View full text |Cite
|
Sign up to set email alerts
|

Depression and its associated factors: perceived stress, social support, substance use and related sociodemographic risk factors in medical school residents in Nairobi, Kenya

Abstract: Background Little data exists regarding depression and its associated factors in medical residents and doctors in Sub-Saharan Africa. Residents are at high risk of developing depression owing to the stressful nature of their medical practice and academic training. Depression in medical residents leads to decreased clinical efficiency, and poor academic performance; it can also lead to substance abuse and suicide. Our primary aim was to measure depression prevalence among medical residents in Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 59 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…Two separate studies of U.S. veterans yielded significant results; they found that individuals with a current PTSD diagnosis reported owning significantly more firearms than those without a current PTSD diagnosis (Freeman & Roca, 2001). Depression -Depression in medical residents leads to decreased clinical efficiency and poor academic performance; it can also lead to suicide (Shah et al, 2021). Depressive disorders are characterized by the presence of sad, empty, or irritable moods, accompanied by somatic and cognitive changes that significantly affect the individual's capacity to function (Shah et al, 2021).…”
Section: Suicide In the Usmentioning
confidence: 99%
See 2 more Smart Citations
“…Two separate studies of U.S. veterans yielded significant results; they found that individuals with a current PTSD diagnosis reported owning significantly more firearms than those without a current PTSD diagnosis (Freeman & Roca, 2001). Depression -Depression in medical residents leads to decreased clinical efficiency and poor academic performance; it can also lead to suicide (Shah et al, 2021). Depressive disorders are characterized by the presence of sad, empty, or irritable moods, accompanied by somatic and cognitive changes that significantly affect the individual's capacity to function (Shah et al, 2021).…”
Section: Suicide In the Usmentioning
confidence: 99%
“…Depression -Depression in medical residents leads to decreased clinical efficiency and poor academic performance; it can also lead to suicide (Shah et al, 2021). Depressive disorders are characterized by the presence of sad, empty, or irritable moods, accompanied by somatic and cognitive changes that significantly affect the individual's capacity to function (Shah et al, 2021). High levels of perceived social support, adequate sleep, and high income may protect against depression (Shah et al, 2021).…”
Section: Suicide In the Usmentioning
confidence: 99%
See 1 more Smart Citation
“…However, of noteworthy is that most of the studies on student stress have been done on medical students 3 , 12 with very few on non-medical students 13 . In Kenya, a study conducted on medical students found 61.6% of the students to have moderate stress 14 while another study on stress and psychosocial adjustment among non-medical students reported that 35.6% had a low score, 27.4% moderate and 37.0% were classified as having high stress levels 13 .…”
Section: Introductionmentioning
confidence: 99%
“…These variables can influence the stress level with an example of exposure to television which has been found to increase stress levels 34 . Other factors that have been found to be associated with stress in students include: smoking, alcohol consumption, insomnia, drug abuse and other psychiatric disorders such as depression 9 , 14 , 35 37 .…”
Section: Introductionmentioning
confidence: 99%